1999
DOI: 10.5737/1181912x927477
|View full text |Cite
|
Sign up to set email alerts
|

Practical support for women with breast cancer

Abstract: Although emotional, social and informational support are well recognized needs among women with breast cancer, practical support has not attracted serious research attention. However, consumer advocates and researchers studying the subjective experience of breast cancer note that practical support may be a particular concern for some women. In order to document some aspects of the practical support issue and begin to render this element of the experience visible, a community-based consumer group conducted a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…A recent study reported that diabetic patients receive unsatisfactory levels of practical information from their doctors 39. Thorne et al40 postulated that information is not provided due to the fact that health care practitioners consider it to be an individual family matter rather than a basic concern of the health care system.…”
Section: Health Care Provider Supportmentioning
confidence: 99%
“…A recent study reported that diabetic patients receive unsatisfactory levels of practical information from their doctors 39. Thorne et al40 postulated that information is not provided due to the fact that health care practitioners consider it to be an individual family matter rather than a basic concern of the health care system.…”
Section: Health Care Provider Supportmentioning
confidence: 99%
“…Most breast cancer patients experience functional limitations while undergoing cancer treatment 1–4. These limitations interfere with roles that they value in their daily lives, known as ‘participation restrictions’ (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, assistance with self‐care can lead to improved quality of life, hope, a sense of optimism, and the ability to deal with the existential aspects of illness 3 . In addition to coping with their own needs, patients with cancer report that they need assistance with helping their family members cope with their emotional needs, physical assistance needs, and shifted functional responsibilities in the family 4 . Furthermore, caregivers' needs often go unmet by healthcare providers in the aftermath of a cancer diagnosis 5 …”
mentioning
confidence: 99%
“…3 In addition to coping with their own needs, patients with cancer report that they need assistance with helping their family members cope with their emotional needs, physical assistance needs, and shifted functional responsibilities in the family. 4 Furthermore, caregivers' needs often go unmet by healthcare providers in the aftermath of a cancer diagnosis. 5 Self-care behaviors and other coping skills can be taught and monitored via Internet-based programs.…”
mentioning
confidence: 99%